Frustration, temperament and social vulnerability in babies: a comparative study - Hernández Escalona, Mery (2021)
Background: Frustration is defined as the body’s responses that are triggered when there is a negative discrepancy between an expected incentive and the one actually received. These situations elicit behavioral, emotional and neurophysiological responses analogous to those that occur with aversive stimuli or their anticipation. There is research on babies, but few on the associations with individual and environmental differences and none on the Argentine population. Objectives: To associate frustration, temperament and social vulnerability in a sample of infants. Method: A comparative associative study was carried out using a structured observation technique where frustration and its relationship with temperament were evaluated in 22 babies aged 10 to 14 months through the infant behavior questionnaire-revised very short form (IBQ-R VSF). The study population belonged to two social strata according to a sociodemographic record. Results: An inverse correlation was found between extroversion and manipulation of objects, and between effortful control and biting response. No significant differences were identified based on the socioeconomic level. Conclusions: The results were discussed taking into account the frustration theory, the study limitations and the recommendations for future research. Authorship contribution MHE: data collection, statistical analysis, final revision of manuscript. AE: study conception and design, data collection. LG: statistical analysis, final revision of manuscript. AM: conception